Adjunctive Statin Therapy Reduces Mortality After Acute Hemorrhagic Stroke - Lin CK; Chen PY; Wu YY; Wu CC; Chen HJ; Liang CL; Lee YC; Lin CW; Hung CM; Wang HK (Dove Medical Press, 2021)
Cheng-Kai Lin,1,2 Po-Yuan Chen,1,2 Yu-ying Wu,1,2 Cheng-Chun Wu,1 Han-Jung Chen,1,2 Cheng-Loong Liang,1,2 Yi-Che Lee,1,3 Chi-Wei Lin,1,4 Chao-Ming Hung,1,5,* Hao-Kuang Wang1,2,6,* 1School of Medicine, College of Medicine, I-Shou University, Kaohsiung, Taiwan; 2Department of Neurosurgery, E-Da Hospital, Kaohsiung, Taiwan; 3Department of Nephrology, E-Da Hospital, Kaohsiung, Taiwan; 4Department of Family Medicine, E-Da Hospital, Kaohsiung, Taiwan; 5Department of General Surgery, E-Da Cancer Hospital, Kaohsiung, Taiwan; 6Department of Neurosurgery, E-Da Cancer Hospital, Kaohsiung, Taiwan*These authors contributed equally to this workCorrespondence: Chao-Ming Hung; Hao-Kuang WangDepartment of Neurosurgery, E-Da Hospital/I-Shou University, No. 1, Yida Road, Jiaosu Village, Yanchao District, Kaohsiung City 82445, TaiwanTel +866-975106080Email ed100647@edah.org.tw; ed101393@gmail.comBackground: Statin treatment improves clinical outcomes in patients with ischemic strokes, although there is no evidence regarding the safety of statin therapy in patients with intracerebral hemorrhage (ICH). This study aimed at evaluating the effects of continuing statin treatment after ICH.Methods: Data were obtained from the National Health Insurance Research Database in Taiwan. We retrospectively compared the data of patients with and without statin exposure after ICH. The outcomes of interest were recurrence of hemorrhagic stroke and mortality during a follow-up period of 10 years.Results: During the 10-year follow-up period, the mortality rate was 32.73% in the statin group and 42.77% in the non-statin group. Statin therapy in patients with acute ICH with dyslipidemia can decrease mortality.Conclusion: Statin therapy reduced the risk of 10-year mortality in patients who experienced acute hemorrhagic stroke.Keywords: statin, hemorrhagic stroke, mortality